How vertical hand movements impact brain activity elicited by literally and metaphorically related words: an ERP study of embodied metaphor - Bardolph, Megan; Coulson, Seana (Frontiers in Human Neuroscience, 2014)
Embodied metaphor theory suggests abstract concepts are metaphorically linked to more experientially basic ones and recruit sensorimotor cortex for their comprehension. To test whether words associated with spatial attributes reactivate traces in sensorimotor cortex, we recorded EEG from the scalp of healthy adults as they read words with while performing a concurrent task involving either upward- or downward- directed arm movements. ERPs were time-locked to words associated with vertical space – either literally (ascend, descend) or metaphorically (inspire, defeat) – as participants made vertical movements that were either congruent or incongruent with the words. Congruency effects emerged 200-300ms after word onset for literal words, but not until after 500ms post-onset for metaphorically related words. Results argue against a strong version of embodied metaphor theory, but support a role for sensorimotor simulation in concrete language.